Evaluation of monitor unit calculation based on measurement and calculation with a simplified Monte Carlo method for passive beam delivery system in proton beam therapy. (8th September 2015) - Hotta, Kenji; Kohno, Ryosuke; Nagafuchi, Kohsuke; Yamaguchi, Hidenori; Tansho, Ryohei; Takada, Yoshihisa; Akimoto, Tetsuo
Abstract : Calibrating the dose per monitor unit (DMU) for individual patients is important to deliver the prescribed dose in radiation therapy. We have developed a DMU calculation method combining measurement data and calculation with a simplified Monte Carlo method for the double scattering system in proton beam therapy at the National Cancer Center Hospital East in Japan. The DMU calculation method determines the clinical DMU by the multiplication of three factors: a beam spreading device factor F BSD, a patient‐specific device factor F PSD, and a field‐size correction factor F FS ( A ) . We compared the calculated and the measured DMU for 75 dose fields in clinical cases. The calculated DMUs were in agreement with measurements in ± 1.1 % for all of 25 fields in prostate cancer cases, and in ± 3 % for 94% of 50 fields in head and neck (H&N) and lung cancer cases, including irregular shape fields and small fields. Although the F BSD in the DMU calculations is dominant as expected, we found that the patient‐specific device factor and field‐size correction also contribute significantly to the calculated DMU. This DMU calculation method will be able to substitute the conventional DMU measurement for the majority of clinical cases with a reasonable calculation time required for clinical use. PACS number: 87.55.kh